ANALYSIS OF STUDENTS’ SCIENCE TEXTBOOKS ON THE SECONDARY SCHOOL LEVEL FOR SCIENTIFIC LITERACY CONTEXT IN HEALTH AND DISEASE TOPICS - Winata Tegar Saputra; Nuryani Y. Rustaman; Lilit Rusyati (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Textbooks are one of the media used in learning science. This study aims to analyze the Indonesian textbooks on health and disease in terms of scientific literacy and socio-scientific issues in content, context, and assessment. The analysis used the review method in the food and digestive system sub-chapter found in eighth graders. It found that the content and context subchapter contains the scientific literacy competency and socio-scientific issues related to Indonesian students' daily lives. While the assessment contains scientific literacy with low to high cognitive demand, it lacks socio-scientific issues. Also, the inquiry aspect of this textbook only contains guided inquiry and lacks open inquiry. Therefore, teachers can adjust that guided inquiry to open inquiries because the curriculum does not prohibit this. This study proposes a learning strategy to improve the ability of students in the scientific literacy aspect to face PISA 2025, with some limitations on analyzing textbooks and the curriculum used nowadays.